Adaptation of a Community Clinical Linkages Intervention to the COVID-19 Pandemic: A Community Case Study - Coulter, Kiera; Ingram, Maia; Lohr, Abby; Figueroa, Carlos; Coronado, Gloria; Espinoza, Cynthia; Esparza, Maria; Monge, Stacey; Velasco, Maria; Itule-Klasen, Lee; Bowen, Magdalena; Wilkinson-Lee, Ada; et al. (Frontiers in Public Health, 2022)
In this community case study, we describe the process within an academic-community partnership of adapting UNIDOS, a community health worker (CHW)-led community-clinical linkage (CCL) intervention targeting Latinx adults in Arizona, to the evolving landscape of Covid-19. Consistent with community-based participatory research (CBPR) principles, academic and community-based partners made decisions regarding changes to the intervention study protocol, specifically the intervention objectives, participant recruitment methods, CHW trainings, data collection measures and management, and mode of intervention delivery. Insights from this case study demonstrate the importance of CBPR in successfully modifying the intervention to the conditions of the pandemic and also the cultural background of Latinx participants. This case study also illustrates how a CHW-led CCL intervention can address social determinants of health (SDOH), in which the pandemic highlighted longstanding inequities along racial and ethnic lines in the United States.